Yeast peptides alleviate lipopolysaccharide-induced intestinal barrier damage in rabbits involving Toll-like receptor signaling pathway modulation and gut microbiota regulation - Fan, Jiaqi; Li, Chong; Han, Wenxiao; Wu, Fengyang; Fan, Huimin; Fan, Dongfeng; Liu, Yajuan; Gu, Zilin; Wang, Yuanyuan; Chen, Saijuan; Chen, Baojiang (Frontiers in Veterinary Science, 2024)
Introduction: Yeast peptides have garnered attention as valuable nutritional modifiers due to their potential health benefits. However, the precise mechanisms underlying their effects remain elusive. This study aims to explore the potential of yeast peptides, when added to diets, to mitigate lipopolysaccharide (LPS)-induced intestinal damage and microbiota alterations in rabbits.Methods: A total of 160 35-day-old Hyla line rabbits (0.96±0.06 kg) were randomly assigned to 4 groups. These groups constituted a 2 × 2 factorial arrangement: basal diet (CON), 100 mg/kg yeast peptide diet (YP), LPS challenge + basal diet (LPS), LPS challenge + 100 mg/kg yeast peptide diet (L-YP). The experiment spanned 35 days, encompassing a 7-day pre-feeding period and a 28-day formal trial.The results indicated that yeast peptides mitigated the intestinal barrier damage induced by LPS, as evidenced by a significant reduction in serum Diamine oxidase and D-lactic acid levels in rabbits in the L-YP group compared to the LPS group (p < 0.05). Furthermore, in the jejunum, the L-YP group exhibited a significantly higher villus height compared to the LPS group (p < 0.05). In comparison to the LPS group, the L-YP rabbits significantly upregulated the expression of Claudin-1, Occludin-1 and ZO-1 in the jejunum (p < 0.05). Compared with the CON group, the YP group significantly reduced the levels of rabbit jejunal inflammatory cytokines (TNF-α, IL-1β and IL-6) and decreased the relative mRNA expression of jejunal signaling pathway-associated inflammatory factors such as TLR4, MyD88, NF-κB and IL-1β (p < 0.05). Additionally, notable changes in the hindgut also included the concentration of SCFA of the YP group was significantly higher than that of the CON group (p < 0.05). 16S RNA sequencing revealed a substantial impact of yeast peptides on the composition of the cecal microbiota.Correlation analyses indicated potential associations of specific gut microbiota with jejunal inflammatory factors, tight junction proteins, and SCFA.In conclusion, yeast peptides have shown promise in mitigating LPS-induced intestinal barrier damage in rabbits through their anti-inflammatory effects, modulation of the gut microbiota, and maintenance of intestinal tight junctions.